BDNF val66met Polymorphism Impairs Hippocampal Long-Term Depression by Down-Regulation of 5-HT3 Receptors - Hao, Rui; Qi, Yu; Hou, Dong-Ni; Ji, Yuan-Yuan; Zheng, Chun-Yan; Li, Chu-Yu; Yung, Wing-Ho; Lu, Bai; Huang, Ying (Frontiers in Cellular Neuroscience, 2017)
Brain-derived neurotrophic factor (BDNF) is a key regulator of neuronal plasticity and cognitive functions. BDNF val66met polymorphism, a human single-nucleotide polymorphism (SNP) in the pro-domain of BDNF gene, is associated with deficits in activity-dependent BDNF secretion and hippocampus-dependent memory. However, the underlying mechanism remains unclear. Here we show that in the BDNFMet/Met mouse line mimicking the human SNP, BDNF expression in the hippocampus was decreased. There was a reduction in the total number of cells in hippocampal CA1 region, while hippocampal expression of mRNAs for NR2a, 2b, GluR1, 2 and GABAARβ3 subunits were up-regulated. Although basal glutamatergic neurotransmission was unaltered, hippocampal long-term depression (LTD) induced by low-frequency stimulation was impaired, which was partially rescued by exogenous application of BDNF. Interestingly, 5-HT3a receptors were down-regulated in the hippocampus of BDNFMet/Met mice, whereas 5-HT2c receptors were up-regulated. Moreover, impaired LTD in BDNFMet/Met mice was reversed by 5-HT3aR agonist. Thus, these observations indicate that BDNF val66met polymorphism changes hippocampal synaptic plasticity via down-regulation of 5-HT3a receptors, which may underlie cognition dysfunction of Met allele carriers.